Maternal Education Level and Child's Anxiety on Dental Extraction - Jeffrey Jeffrey; Florence Meliawaty; Asih Rahaju (Journal of Medicine and Health, 2018)
Dental extraction can cause anxiety in children, observed in vital signs changes. If occursexcessively, it can be regarded as an obstacle and may affect a child's behavior that can furtherdetermine the success of dental treatment. Anxiety that occurs in children can usually be influencedby various factors, including the level of parental education. This study aimed to observe maternaleducation level and anxiety in children receiving dental extraction treatments. This is a descriptivestudy, involving 60 subjects aged 7-12 that went for dental extraction at Rumah Sakit Gigi MulutPendidikan Universitas Jenderal Achmad Yani (RSGMP UNJANI) Cimahi Juli-Desember 2016. Theparameters examined for measuring anxiety are body temperature, respiration frequency, and pulsebefore and after the procedure. This study found that 63.3% of mother of the subject had high schooleducation, 16.7% of junior high school, 8.3% S1, 6.7% D1/D3, and 5% SD. Increased bodytemperature was obtained in 36 subjects, increased respiration frequency in 46 subjects, andincreased pulse in 34 subjects. We concluded that the majority of maternal education levels in thisstudy are high school graduates and the anxiety parameters in the majority of subjects increase whenreceiving dental extraction procedure.Keywords: child's anxiety, dental extraction, mother education level